Support for social entrepreneurship in Poland under the European Social Fund – changes and challenges - Kruk, Marzena (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
he European Commission directs its financial instruments to the broadly understood social economy sector, including the development of social entrepreneurship. In 2011, the European Commission presented the Social Business Initiative (SBI), defining the activities of the European Union to support the development of social enterprises (key stakeholders of the social economy). According to the assumptions of the European Commission, social enterprises are specific organisations that combine social objectives with initiatives promoting entrepreneurial attitudes, focusing on achieving wider social goals or exerting social impact. Financial support is also intended to generate changes in a broader time perspective in the coming years of the EP’s activity. Since Poland’s accession to the European community in 2004, the social economy (including social enterprises) has received financial support in many areas of its activity. The beneficiaries of the funds covered not only social economy entities (PES), but also institutions supporting the development of the social economy, mainly social entrepreneurship, such as Social Economy Support Centers (OWES). It is mainly these key entities of the social economy - social enterprises have become places of new jobs and motivators of civic activity. The aim of the article is to quantify the financial support received from the European Social Fund in the years 2004-2016 for activities aimed at the development of social entrepreneurship (SE).